S
Sarah
I received help with a formula problem from this newsgroup
yesterday which gave me this formula
=(COUNT(D4:E4)=2)*(1*(D4=E4)+3*(D4>E4))+(COUNT(F4:G4)=2)*
(1*(F4=G4)+3*(F4>G4))+(COUNT(H4:I4)=2)*(1*(H4=I4)+3*(H4>I4)
+(COUNT(J4:K4)=2)*(1*(J4=K4)+3*(J4>K4)+(COUNT(L4:M4)=2)*(1*
(L4=M4)+3*(L4>M4))))
How can I now add to this so that if D4<E4 & F4<G4 & H4<I4
& J4<K4 & L4<M4, then the figure 1 is added each time into
a completely different cell e.g. P4. Therefore if D4<E4
and J4<K4 I would expect to see the figure 2 in cell P4.
Thank you for any help you can give!
yesterday which gave me this formula
=(COUNT(D4:E4)=2)*(1*(D4=E4)+3*(D4>E4))+(COUNT(F4:G4)=2)*
(1*(F4=G4)+3*(F4>G4))+(COUNT(H4:I4)=2)*(1*(H4=I4)+3*(H4>I4)
+(COUNT(J4:K4)=2)*(1*(J4=K4)+3*(J4>K4)+(COUNT(L4:M4)=2)*(1*
(L4=M4)+3*(L4>M4))))
How can I now add to this so that if D4<E4 & F4<G4 & H4<I4
& J4<K4 & L4<M4, then the figure 1 is added each time into
a completely different cell e.g. P4. Therefore if D4<E4
and J4<K4 I would expect to see the figure 2 in cell P4.
Thank you for any help you can give!